Assessment of Risk Factors in Atherosclerotic Saudi Patients above 40 Year Old in King Khalid Hospital in Najran - Al-Faran, Fahad; Omar alshahrani, Hussain, Alsaihab, Rakan Aldosari, Waleed Aldosari, Mobark Aldosari, Ashaq Alqhtani; Albakri Fahad, Fatimah Almsaud, Ali Alhassan, Mohammed Homood, Abdullah Alshareef (International Journal of Innovative Research in Medical Science, 2017)
Atherosclerosis is a disease in which plaque builds up inside arteries. Plaque is made up of fat, cholesterol, calcium, and other substances found in the blood. Over time, plaque hardens and enlarge. This limits the flow of oxygen-rich blood to organs supplied by the affected artery. Atherosclerosis can affect any artery in the body, including arteries in the heart, brain, arms, legs, pelvis, and kidneys. As a result, different diseases may develop based on which arteries are affected. The cause of atherosclerosis isn't known. However, certain traits, conditions, or habits may raise risk for the disease. These conditions are known as risk factors such as smoking, age, gender…etc. A facility- based descriptive case series study will be conducted in King Khalid Hospital in Najran City to assess risk factors in atherosclerotic Saudi Patients above 40 years old. Case series and selective sampling techniques will be used for the selection of 50 atherosclerotic Saudi Patients above 40 years old. The data will be collected by structural interview (check-list). Data processing and analysis will be done by entering the data into SPSS for Windows7. My results show that most age group affected by atherosclerosis are from 60-69, also patients effected by atherosclerosis have no dyslipidemia about 64%. Patients affected by atherosclerosis are diabetes about 65.31%, while we found the duration of diabetes in most atherosclerotic Saudi patients from (6-10 years), (16-10 years) about 29.1%. But patients with atherosclerosis have no stroke 74%. The patients with atherosclerosis are not smoker about 90%. Most atherosclerotic Saudi patients with diabetes are male about 51.02%., also most atherosclerotic Saudi patients with hypertension are male about 48%. Atherosclerotic Saudi patients with obesity are female about 22%. The most atherosclerotic Saudi patients with dyslipidemia are female about 26%, and the atherosclerotic Saudi patients with stroke are from age 60-69 years old. The atherosclerotic Saudi patients are somker from age 60-79 years old.